Optimization of the Irrigated Cropping Pattern in Fars Province to Adapt to Water Scarcity - A. Mirzaei; A. Soltani; F. Abbasi; E. Zeinali; Sh. Mirkarimi (علوم آب و خاک)
Water scarcity and adaptation to it are the most significant issues facing Iran's agriculture. Optimizing the cropping pattern is one of the fundamental strategies for addressing water scarcity. This study evaluated the optimization of the cropping pattern in the irrigated lands of Fars province, one of Iran's key agricultural production areas. Linear mathematical programming and the SAWA system (System for Provincial Agricultural Water Balance and Accounting) were employed. The optimal cropping pattern (OCP) was designed to minimize applied irrigation water and was compared with the current cropping pattern (CCP) as well as a proposed cropping pattern from the Agricultural Jahad Organization (CPAJO) for the province for the cropping year 2023-2024. The results indicated that in the OCP, compared to the CCP, the cultivated area for the following crops decreased: wheat by 30%, barley, grain maize, silage maize, alfalfa, sugar beet, potato, cold- season legumes, and cold-season oil crops by 60%, rice by 80%, warm-season fruit trees by 42%, and vegetables by 13%. Conversely, the cultivated area for warm-season legumes and cold-season fruit trees each increased by 60%, while cold-season legumes increased by 150%. To meet the adaptation goals for water scarcity and sustainable agriculture outlined in this study, a 24% reduction in the irrigated cultivation area of the province was deemed necessary. The OCP achieved a 34% reduction in applied irrigation water at the provincial level without decreasing farmers' income. Compared to the CCP, the OCP led to a 32% reduction in the amount of plant production (by weight) at the provincial level. However, prioritizing plants with higher gross economic profit and lower water consumption over those with lower gross economic profit and higher consumption resulted in the gross economic return of the OCP being comparable to that of the CCP and the CPAJO. The comparison of OCP with CPAJO indicated that the CPAJO has not seriously considered adaptability to water scarcity or agricultural sustainability. The CPAJO needs to be reviewed and optimized to address water scarcity and ensure production stability in light of the impacts of excessive water withdrawal in the province.